I need help for this question anybody answer
Attachments:
![](https://hi-static.z-dn.net/files/d17/30a18a59c32fe748a3f1dc8c40618628.jpg)
Answers
Answered by
4
Answer:
0
Step-by-step explanation:
IMPORTANT FORMULA:
(a + b)³ = a³ + b³ + 3ab(a + b)
(a - b)³ = a³ - b³ - 3ab(a - b)
p = 2 - a
a³ + 6 ap + p³ - 8
= a³ + 6 a(2 - a) + (2 - a)³ - 8
= a³ + 12a - 6 a² + { 2³ - a³ - 3x2x a (2 - a)} - 8
= a³ + 12a - 6 a² + { 8 - a³ - 6 a (2 - a)} - 8
= a³ + 12a - 6 a² + { 8 - a³ - 12 a + 6a² } - 8
= a³ + 12a - 6 a² + 8 - a³ - 12 a + 6a² - 8
= a³ - a³ + 12a - 12a - 6a² + 6a² + 8 - 8
= 0
Hope it helps you.
Thanks
Similar questions